Attitude of upland farmers on loan repayment study in Central Negros - Velasco, Manuel
One of the basic problems of the Philippines today is its widespread poverty. Translated into concrete figures, there are about 27.60 million Filipinos living below the poverty threshold. To address this issue, government agencies including non-governmental organizations and other private voluntary groups has embarked on livelihood program. Among the common strategy adopted by these groups is the implementation of credit assistance which is geared towards the vision of sustainability in order to resolve poverty. Based on experiences however, credit programs seemed to be problematique option because of the so many issues relating to repayment. Thus, this research study. Cognizant of the strategic role of livelihood program to the issue of poverty alleviation and the attitudes on the repayment to the sustainability of the credit project, the problem of this research study is to determine whether the Filipino values of utang na loob, hiya and dangal and the characteristics of lending institutions such as offering of services to borrowers, employment of credit collectors, timing of of collection by the collectors, charging of high interest rates, and imposing of penalty on past due loans have effects on the attitude of upland farmers toward loan repayment. Thus, the objective of the study is to determine the effects of Filipino values and the characteristics of lending institution on the attitude of upland farmers toward loan repayment. The hypotheses of this study are : (1) that the Filipino values are not related to the attitudes and (2) that the characteristics of lending institution are not related to the attitudes of upland farmers toward loan repayment. The research design of this study followed the descriptive research method. Respondents were determined using the probability sampling (stratified and random sampling techniques) and non-probability sampling (purposive sampling technique) methods. Sample size is 30% of the population of the identified research area in Central Negros district. Data gathering was made through interviews using the standardized interview method (use of questionnaire). The statistical tool used for the analysis of data was the Chi-square test. The following are the research results of this study : A. Effects of the Filipino values on the attitude of upland farmers. Though the data implied that majority of the upland farmers agreed (strongly agree or agree) on the following Filipino value : (1) of utang na loob (looking up to debt of gratitude, obligation to reciprocate for the favors received and being walang utang na loob for not repaying of utang na loob) ; (2) of hiya (being ashamed for not complying the loan obligations, being embarrassed to themselves, family and friends for filing to settle loans and feeling guilty for not complying responsibilities) ; and, (3) of dangal (diminishing of dignity for not repaying the loan, decreasing of respect to themselves for not paying the loan and degrading and worthiness for not settling the loan obligation on time). statistical analysis using the chi-square tests concluded that only utang na loob is significantly related to the attitude of upland farmers. The two other values were found to be not significantly related to the attitude of the farmers. This means that only utang na loob have effects on the attitude of upland farmers towards loan repayment while hiya and dangal do not have significant effects on the attitude of farmers. Relating the three filipino values with the demographic (intervening) factors of sex, educational attainment, family size and monthly family income, declares the acceptance of the null hypothesis in all the Chi-square tests. again, though the research results tend to inform that majority are agreeable on the statements, statistical analysis proved otherwise. The results stated that all the demographic factor are not significantly related to the attitude of the farmers. Moreover, this connotes that sex, educational attainment, family size and family income does not influence the three Filipino values to have significant effects on the attitudes of the farmers. B. Effects of the characteristics of lending institution on the attitude of upland farmers. Based on the results, majority of the upland farmers agreed (strongly agree or agree) that the characteristics of lending institution such as offering of services to borrowers, charging of high interest rates and imposing of penalty on past due loans could positively influence their attitude towards repayment. looking at the data, this study tend to create an impression that the identified characteristics have effects on the attitudes. However, statistical analysis declared that none of the said characteristics are significantly related to the attitudes as manifested by the acceptance of null hypothesis in all the tests done. Thus, this study concludes that the aforementioned characteristics of lending institution are not factors that could influence the attitudes of upland farmers towards loan repayment. Furthermore, this shows that the five characteristics of lending institution does not have significant effects on the attitudes of the farmers. Relating the five characteristics of lending institution to the intervening factors of sex and educational attainment, all the Chi-square tests done conferred the acceptance of the null hypothesis. similarly, though the data showed that majority are agreeing on the statements, statistical test confirmed that sex and educational attainment are not significantly related to the five characteristics of the lending institution. Therefore, this study concludes that in terms of sex and educational attainment, the five characteristics of lending institution does not have significant effects on the attitude of upland farmers on towards loan repayment. Finally, this study recommends for a follow up research on this matter particularly looking deeper into the other dimensions of the said Filipino values. the other aspect of the study should dwell on the issues that may be relevant to the determination of factors that may influence the attitude of upland farmers on loan repayment.